According to forensic science recommendations, are carbon dots capable of reliably developing latent fingerprints? - da Silva Carvalho, Daniel; Lobo, Bernardo José Munhoz; da Silva, Atailson Oliveira; Sousa, Marcelo Henrique; da Silva, Sebastião William (Forensic science international, 2024)
Carbon dots (CDs) are zero-dimensional carbon nanomaterials that have been subject of considerable interest due to their remarkable electronic and optical characteristics. Their adjustable properties have gathered attention in different fields, including biological sensing, drug delivery, photodynamic therapy, photocatalysis, solar cells, and latent fingerprint development. In forensic science, the frequently reported outstanding photoluminescence behavior and biocompatibility of CDs are particularly important. Therefore, the objective of this systematic review was to assess the reliability of the results presented in studies proposing CD-based solutions for latent fingerprint development. By standardizing procedures, forensic science guidelines are valuable references that provide a framework for comparing new development materials with established ones. These publications were used to generate key points that allowed for a more objective evaluation of the reviewed studies. Our analysis revealed that most of the studies were conducted under rather limited conditions, with significant potential for bias in the presentation and evaluation of the new results achieved by the new CD-based developmental materials. •Critical analysis of the strengths and weaknesses related to the development of fingermarks using carbon dots (CDs).•Research that presents CDs as an option for fingermark development fails to consider the recommendations of forensic science.•Significant room for bias and potential reliability issues in the application of CDs for fingermark development.